Trend of morbidity and mortality indicators due to acute diarrheal disease in children under five years old in the State of Piauí (2000-2019) - Rafael Everton Assunção Ribeiro da Costa; Ana Raquel Lopes Visgueira; Ranieri Flávio Viana de Sousa; Kerla Joeline Lima Monteiro; Marco Aurelio Pereira Horta; Beatriz Fátima Alves de Oliveira (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze the trend of morbidity and mortality indicators due to acute diarrheal diseases in children under five years old in Piauí. Methods: ecological study with data from the Information Technology Department at the Public Health System. The indicators of hospitalization rate and coefficient of mortality from the disease between 2000 and 2019 were calculated. A descriptive analysis of the indicators was carried out in the studied period and by the macro-regions in the State. For trend analysis, the simple linear regression model with log-transformation was used. Trends were classified as increasing, decreasing and stable, with a significance level of 5%. Results: the average on hospitalization rate was higher in the semi-arid macro-region (36.6/1000 children under five years old) and lower in Teresina (14.9/1000 children under five years old). The mean mortality coefficients were higher in the coastal macro-region (0.98/1000 live births) and lower in Teresina (0.47/1000 live births). The indicators showed a downward trend in all analyzed locations (p<0.05). A turning point was noted from 2009, with a significant reduction in hospitalization rates in the savanna and semi-arid macro-regions. Conclusion: indicators of morbidity and mortality due to acute diarrheal diseases in children under five years old showed a downward trend in Piauí between 2000 and 2019, with differences in trends between the evaluated macro-regions.